Factor taxation, income distribution, and capital market integration - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
The paper analyzes the optimal mix of capital and wage taxation when policymakers maximize the political support of workers and capitalists, subject to a fixed revenue requirement. Capital market integration increases the efficiency costs of a tax on capital but simultaneously changes the political equilibrium through its effect on the distribution of factor incomes. These distributional effects are directly opposed in the capital importing and the capital exporting region. While the capital tax rate will always be lowered in the capital importing region, the tax rate in the exporting country will rise when the political resistance to market-induced changes in the distribution of income is sufficiently high.
Keywords: H21; H22; F15; D33; 330; capital tax competition; income distribution